A novel recession rate physics methodology for space applications at CIRA by means of CIRCE radioactive beam tracers. (12th February 2018) - De Cesare, M; Di Leva, A; Del Vecchio, A; Gialanella, L
Abstract: Thermal protection systems (TPSs) of spacecrafts, either for single use or reusable, experience wear by ablation and erosion, due to the high heat fluxes during a re-entry phase in the atmosphere. The determination of the wear rate is a crucial point, which is presently mainly possible in aerospace on-ground measurements by means of invasive diagnostics. The purpose of this paper is to present novel contactless, online, high-sensitivity and non-intrusive diagnostics for wear measurements based on radioactive tracers. We propose the technique for future on-ground experiments that might later be developed to perform in-flight TPSs monitoring, thus significantly increasing the safety of the aerospace vehicles. The basic ideas of the method, its sensitivity investigated by GEANT4 simulations, and the future experimental validation are outlined.